MANAJEMEN KURIKULUM DI MADRASAH ALIYAH (PENELITIAN DI MA YPPA CIPULUS) - Siti Patimah, Tati; Herliani, Heni; Sugandi, Moh; Lukmanul Jamil, Zam zam (Expectation: Journal of Islamic Education Management, 2024)
This curriculum management is beneficial not only for educators but also for students. Educators see the curriculum as an organization of learning experiences, with students as "consumers". In this way, it is hoped that students can gain a number of new experiences that can be added along with developments over time. Curriculum management is an important part of the overall educational process because without it nothing possible to realize educational goals optimally. Thus, without good management, an educational institution will not be able to achieve its educational goals well. The Independent Learning Curriculum is a policy established by the Minister of Education and Culture to provide students with the opportunity to choose the courses they want and encourage them to acquire the knowledge necessary for their future keywords: management, curriculum management, independent curriculum